Exploring Saudi Arabia’s care economy in health, education, and social care: a textual analysis using the care diamond framework - AlSaif, Atheer Khalid; AlMubarak, Sama'a Hamed; Albagmi, Faisal Mashel (Frontiers in Public Health, 2025)
ObjectiveThe study delineated the care economy in the context of Saudi Arabia by systematically exploring its structure, coordination, and challenges, focusing on healthcare, education, and social care through Razavi’s Care Diamond framework.MethodsA qualitative design with deductive textual analysis was employed to analyse 40 sources (34 webpages, 6 policy documents) from the state, market, community, and family sectors. Purposive sampling identified materials most likely to provide policy-relevant insights. Braun and Clarke’s six-phase thematic analysis guided coding, with NVivo used to organize and synthesise sectoral roles, overlaps, and gaps.ResultsThe study identified five interrelated themes: (1) absence of a formal care economy structure, with the concept absent from policy discourse; (2) state dominance as the primary architect of care across all domains, but with fragmented coordination; (3) market sector participation concentrated in high-cost healthcare, with minimal education and no social care involvement; (4) family’s critical but unrecognized role, particularly unpaid caregiving by women, indirectly addressed through employment subsidies; and (5) community sector contributions filling care gaps but remaining inconsistent and under-supported. The analysis revealed strong state control but weak integration across sectors, resulting in duplication, inefficiencies, and the marginalisation of unpaid and community-based care.ConclusionSaudi Arabia’s care economy is characterised by state dominance, sectoral imbalance, and fragmented delivery. Formal recognition of all four care diamond sectors, integration of unpaid care into policy, and cross-sectoral coordination are essential to achieving Vision 2030 goals.